Trends in subtrochanteric, diaphyseal, and distal femur fractures, 1984–2007 - Ng, A. C. (2011)
SUMMARY: The incidence of non-hip femur fractures increased between 1984 and 2007, with an increase in the rates for women after 1996. INTRODUCTION: Recent reports have suggested that non-hip femur fractures may be decreasing over time, similar to proximal femur fractures. METHODS: Incidence rates for non-hip femur fractures among Olmsted County, Minnesota, residents were assessed before and after 1995 when the oral bisphosphonate, alendronate, was approved in the USA. RESULTS: From 1984 to 2007, 727 non-hip femur fractures were observed in 690 Olmsted County residents (51% female [median age, 71.6 years] and 49% male [21.4 years]). Altogether, 20% of the fractures were subtrochanteric, 51% were diaphyseal, and 29% involved the distal femur. Causes included severe trauma in 51%, minimal to moderate trauma in 34%, and pathologic causes in 15%. The overall age- and sex-adjusted annual incidence of first non-hip femur fracture was 26.7 per 100,000 (25.0 per 100,000 for women and 26.6 per 100,000 for men). Incidence rates increased with age and were greater in women than men. Between 1984–1995 and 1996–2007, age-adjusted rates increased significantly for women (20.4 vs. 28.7 per 100,000; p=0.002) but not for men (22.4 vs. 29.5 per 100,000; p=0.202). CONCLUSION: The incidence of first non-hip femur fractures rose between 1984 and 2007, with an increase in the rates for women after 1995.